Fungal bioremediation of soil co-contaminated with petroleum hydrocarbons and toxic metals - Li, Qianwei (Appl Microbiol Biotechnol, 2020)
ABSTRACT: Much research has been carried out on the bacterial bioremediation of soil contaminated with petroleum hydrocarbons and toxic metals but much less is known about the potential of fungi in sites that are co-contaminated with both classes of pollutants. This article documents the roles of fungi in soil polluted with both petroleum hydrocarbons and toxic metals as well as the mechanisms involved in the biotransformation of such substances. Soil characteristics (e.g., structural components, pH, and temperature) and intracellular or excreted extracellular enzymes and metabolites are crucial factors which affect the efficiency of combined pollutant transformations. At present, bioremediation of soil co-contaminated with petroleum hydrocarbons and toxic metals is mostly focused on the removal, detoxification, or degradation efficiency of single or composite pollutants of each type. Little research has been carried out on the metabolism of fungi in response to complex pollutant stress. To overcome current bottlenecks in understanding fungal bioremediation, the potential of new approaches, e.g., gradient diffusion film technology (DGT) and metabolomics, is also discussed. KEY POINTS: • Fungi play important roles in soil co-contaminated with TPH and toxic metals. • Soil characteristics, enzymes, and metabolites are major factors in bioremediation. • DGT and metabolomics can be applied to overcome current bottlenecks.